The Oxford Encyclopedia of Crisis Analysis : Volume 1 (A-H) & 2 (I-W) - Stern, Eric K. (New York: Oxford University Press, 2022)
"Contemporary societies are increasingly crisis-prone and crises have profound implications for the rapidly changing political, economic, and social landscape. Crises pose major challenges to governments, communities, leaders and organizations. The Oxford Encyclopedia of Crisis Analysis provides a comprehensive overview of the rapidly emerging and evolving field of crisis studies and explores its connection to a number of relevant neighboring fields of knowledge. Crises are complex, unfold in diverse political and socio-technical contexts and must be studied and understood from multiple angles and disciplinary perspectives. This Encyclopedia brings together contributions by experts from political science, public administration, management, international relations, public health, sociology, economics, media and mass communications, the law and many other fields to explore important theoretical, methodological, empirical, and practical issues related to crisis and crisis management. Articles focus on concepts (crisis as well as closely related concepts such as emergency, disaster, resilience, security etc.), contingencies (natural hazards, major accidents, pandemics, terrorism, social and political conflict among many others), historical and contemporary cases, classic and cutting edge research methods, different "phases" of the crisis/emergency management cycle, as well as documenting a wide range pitfalls and good practices that can help to forewarn and forearm current and future crisis managers"--
Volume 1. A-H -- Volume 2. I-W.
Includes bibliographical references and index.
Keywords: Crisis management -- Encyclopedias; Emergency management -- Encyclopedias